Method Development and Validation for Quantification of Potential Genotoxic Impurity, PyCl in Lansoprazole Hydrochloride using Liquid Chromatography Combined with Mass Spectrometry - Purushotham Reddy, C.; Venkateswara Rao, G.; Ramakrishna, K.; Narayana Rao, K.M.V. (Asian Journal of Chemistry, 2021)
A sensitive and robust high performance liquid chromatography combined with tandem mass spectrometry (LC-MS/MS) method was developed and validated for the determination of potential genotoxic impurity (PGI), 2-(chloromethyl)-3-methyl-4-(2,2,2-trifluoroethoxy)-pyridine hydrochloride (PyCl) in lansoprazole as per ICH Q2 guideline. In this method, PyCl and lansoprazole were well-separated from each other on Acquity UPLC BEH-C18 column (50 × 4.6 mm × 1.7 μ) in a gradient elution mode with the mobile phase consisting of 0.1% formic acid in water (mobile phase-A) and acetonitrile (mobile phase-B) at a flow rate of 0.4 mL/min. For the quantitation of Py-Cl, selective ion monitoring (SIM) mode was used with m/z 240 ion in LC-MS method. The validated method was found to be precise, accurate and linear from the range of LOQ level to 150% with respect to sample concentration and the correlation co-efficient was found to be 0.998. Limit of detection (LOD) and limit of quantifications (LOQ) were found to be 0.000012 and 0.000004 mg/mL, respectively. The validated method was found to be sensitive and the recoveries were found to be well within the range from 83.4% to 95.9% for Py-Cl. Further, the solution stability was also established as the same were found to be stable upto 24 h.